Vision, race, and modernity : a visual economy of the Andean image world - Poole, Deborah (Princeton studies in culture/power/history., 1997)
"Long-awaited work analyzes role of visual images and technologies (particularly photography, painting, and drawing) in shaping modern understandings of race in the Andes. This fascinating work documents various depictions of Andean peoples from the 18th - 20th centuries, placing scientific analyses of race within the sphere of the modern visual economy"--Handbook of Latin American Studies, v. 57.